SME Internal Control: How is compliance with COSO Framework? - Setyawan, Bimo; Indah Riwajanti, Nur; Dewi Sri Susilowati, Kartika (Dinasti Publisher, 2021)
Malang, East Java Indonesia, is a tourist city with natural beauty and a large variety of food and beverage industries, including Coffee Shops. The purpose of this study was to evaluate the compliance of the internal control implementation of the SMEs (Small Medium Enterprises) food and beverage based on the COSO Framework. This research is qualitative research with a case study method that uses components of the COSO Framework as basis analysis of four coffee shops in Malang City. The results show that there are differences between theory and practice in the field. Generally, among five components of the COSO Framework, the Control Activities component has not been considered important in internal control. Hence, there are some cases of irregularities that create or negligence in each coffee shop. It can be concluded that SME still need control over their business to eliminate fraud; therefore, separation of duties is required.